2002
DOI: 10.1677/joe.0.1730493
|View full text |Cite
|
Sign up to set email alerts
|

Implication of alpha4 phosphoprotein and the rapamycin-sensitive mammalian target-of-rapamycin pathway in prolactin receptor signalling

Abstract: A prolactin (PRL)-responsive 3 -end cDNA encoding rat 4 phosphoprotein was previously isolated from a rat lymphoma cDNA library. Rat 4 is a homologue of yeast Tap42 and is a component of the mammalian target-ofrapamycin (mTOR) signalling pathway that stimulates translation initiation and G1 progression in response to nutrients and growth factors. In the present study, the full-length rat 4 cDNA was obtained by 5 -RACE and the 1023 bp open reading frame predicted a 340 amino acid protein of 39·1 kDa. The 4 mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…by rapamycin pointed to a possible interaction between the PRLR and mTOR pathways. We have shown that rapamycin partially inhibited Nb2 cell proliferation, but crosstalk between the PRL and mTOR pathways was further supported by our observation that overexpressed a4 phosphoprotein, a component in the mTOR pathway, inhibited PRL-stimulated IRF-1 promoter activity in transfected COS-1 cells (Boudreau et al 2002). In the murine L2 clonal T-cell line, which requires both interleukin 2 (IL2) and PRL for proliferation, rapamycin, and PI3K inhibitors (wortmannin and LY294002), markedly inhibited IL2-induced cell proliferation and nuclear translocation of PRL (Belkowski et al 1999).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…by rapamycin pointed to a possible interaction between the PRLR and mTOR pathways. We have shown that rapamycin partially inhibited Nb2 cell proliferation, but crosstalk between the PRL and mTOR pathways was further supported by our observation that overexpressed a4 phosphoprotein, a component in the mTOR pathway, inhibited PRL-stimulated IRF-1 promoter activity in transfected COS-1 cells (Boudreau et al 2002). In the murine L2 clonal T-cell line, which requires both interleukin 2 (IL2) and PRL for proliferation, rapamycin, and PI3K inhibitors (wortmannin and LY294002), markedly inhibited IL2-induced cell proliferation and nuclear translocation of PRL (Belkowski et al 1999).…”
Section: Discussionsupporting
confidence: 65%
“…We have observed that rapamycin alone did not completely abolish, but only partially inhibited the PRL stimulation of Nb2 cell proliferation by 50% (Boudreau et al 2002). PRL has also been reported to stimulate the activity of MAPK before that of S6K (i.e.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…[136][137][138][139] Separate studies suggested that prolactin stimulates mTOR, and modifies STAT1 activity in mTOR-dependent fashion. 140,141 Further studies are required to better understand how mTORCs interact with androgen or estrogen signaling pathways.…”
Section: Other Emerging Mtor Targets In Lammentioning
confidence: 99%